Information Overload: Causes, Consequences and Remedies - A Study (Philosophy and Progress, 2016)
Information overload, usually characterized by an over abundance of information, is a major cause of concern for general information users, researchers and information managers. With the advent of new technological innovations, the rate of information production has accelerated rapidly. Consequently, people are suffering from an information glut, which makes it difficult for them to find the required information quickly and conveniently from various print, electronic and online sources. The paper analyzed the causes and causes of information overload in the 21st century and puts forward suggestions for overcoming this problem. It stresses the importance of concerted efforts from information professionals, computer scientists and academics to devise techniques and technologies for countering the effects of information overload.Philosophy and Progress, Vol#55-56; No#1-2; Jan-Dec 2014